IMPLEMENTATION OF THE PROBLEM-BASED LEARNING MODEL IN IMPROVING PRIMARY SCHOOL STUDENTS' CRITICAL THINKING ABILITIES - Rian Permana Suryadipraja; Rahman Tanjung (International Journal of Teaching and Learning, 2026)
This research aims to explore the implementation of the Problem-Based Learning (PBL) learning model in improving elementary school students' critical thinking skills through a literature review. The research method used is literature analysis from various scientific articles, journals and other trusted sources related to PBL and critical thinking in elementary school students. The research results show that PBL is effective in developing critical thinking skills through student-centered learning, the use of real-world problems as learning stimuli, and the application of collaborative strategies. Several factors that support the success of PBL include relevant problem design, support and facilitation from teachers, and ongoing evaluation with constructive feedback. This study confirms that PBL not only improves students' cognitive skills, but also motivates and arouses their interest in learning, thereby creating a more dynamic and interactive learning environment. Based on the results of this literature review, it is recommended that the implementation of PBL be further expanded and facilitated through teacher training to increase its effectiveness in supporting the development of critical thinking in elementary school students.